Effectiveness of a Psychoeducational Guidance Service Package in Enhancing Elementary Students’ Learning Motivation - Musfirah (International Journal of Technology and Education Research, 2025)
This study aimed to develop and examine the effectiveness of a psychoeducational guidance service package designed to enhance elementary students’ learning motivation. Using a Research and Development approach with the 4D model (Define, Design, Develop, and Disseminate), the product was constructed based on a needs analysis, validated by content and media experts, and tested through small-group and limited field trials. A quasi-experimental nonequivalent control group design was employed to measure effectiveness, involving 44 students in the experimental group and 38 students in the control group from two public elementary schools in Parepare City, Indonesia. Data were collected using expert validation sheets, practicality questionnaires, and a motivation scale, and analyzed with descriptive statistics and inferential tests. The results demonstrated that the developed psychoeducational package met the criteria of validity and practicality and was proven effective in increasing students’ motivation. Independent samples t-test results indicated a significant difference between the experimental and control groups (p = 0.000 < 0.05; tₕ = 5.336 > tₜ = 1.663), with the experimental group showing a substantial improvement from low and moderate motivation levels during the pretest to high levels in the posttest. These findings confirm that structured psychoeducational guidance can significantly improve learning motivation and provide a feasible solution for elementary schools lacking professional counseling services.